PENGARUH KONSENTRASI DAN LAMA PERENDAMAN ASAM SULFAT TERHADAP PERKECAMBAHAN BENIH DELIMA MERAH (Punica granatum L.) - Rita Elfianis; Nadia Putri; Syukria Ikhsan Zam (Jurnal Agroteknologi, 2023)
The problem of propagation of Punica granatum, was hard seed, and it difficult to germinate. One of the efforts to solve the problem is using H2SO4 as to breakdown of the hard seed. This study aimed to obtain the best concentration of H2SO4 and soaking time, as well as the interaction between H2SO4 concentration and soaking time on the germination ofÂ  Punica granatum seeds. This study used a completely randomized design (CRD) consisting of 2 factors. The first factor is H2SO4 concentration (0%, 20%, 40%, 60%, and 80%), and the second factor is soaking time (10, 15, and 20 minutes). Parameters observed were germination, germination rate, vigor index, germination height, root length, weight of sprouts, and dry weight of Punica granatum sprouts. The results showed the use of water was the best treatment on germination (85.30%), germination rate (17.37 days), vigor index (2.24%), germination height (7.80 cm), and root length of Punica granatum (7.05 cm), soaking time did not effect the germination of Punica granatum, and the interaction between the use of water and the soaking time 15 minutes was the best treatment on the parameters of fresh weight of sprouts (0.17 g) and dry weight of Punica granatum sprouts (0.13 g).